A comparison of the effects of clozapine and its metabolite norclozapine on metabolic dysregulation in rodent models. (15th September 2020) - Yuen, J.W.Y.; Wu, C.; Wang, C.K.; Kim, D.D.; Procyshyn, R.M.; Honer, W.G.; Barr, A.M.
Abstract: Rationale: The second generation antipsychotic drug clozapine is a psychotherapeutic agent with superior efficacy for treatment-resistant schizophrenia. Clozapine is associated with a low likelihood of neurological side-effects, but a high propensity to induce weight gain and metabolic dysregulation. The primary metabolite of clozapine is norclozapine (N-Desmethylclozapine), which has psychoactive properties itself, but its effects on metabolic function remains unknown. The goal of the present study was to determine whether directly administered norclozapine could cause metabolic dysregulation, similar to clozapine. Methods: Adult female rats were treated with a range of doses of clozapine and norclozapine (0.5, 2, 8 & 20 mg/kg, i.p.) and then subjected to the intraperitoneal glucose tolerance test (IGTT), where glucose levels were recorded for 2 h following a glucose challenge. In parallel, rats were tested with two doses of clozapine and norclozapine (2 & 20 mg/kg, i.p.) in the hyperinsulinemic-euglycemic clamp (HIEC), to measure whole body insulin resistance. Results: In the IGTT, clozapine demonstrated dose-dependent effects on fasting glucose levels and total glucose area-under-the-curve following the glucose challenge, with the two highest doses strongly increasing glucose levels. Only the highest dose of norclozapine increased fasting glucose levels, and caused a non-significant increase in glucose levels following the challenge. By contrast, both doses of clozapine and norclozapine caused a potent and long-lasting decrease in the glucose infusion rate in the HIEC, indicating that both compounds cause whole body insulin resistance. Abstract: While not as potent as its parent compound, norclozapine clearly exerts acute metabolic effects, particularly on insulin resistance. This article is part of the issue entitled 'Special Issue on Antipsychotics'. Highlights: Clozapine increased fasting glucose levels and caused glucose intolerance. Norclozapine increased fasting glucose only at the highest dose. Both drugs caused potent and long-lasting whole body insulin resistance.